Differential Prognostic Indicators for Locoregional Recurrence, Distant Recurrence, and Death of Breast Cancer. (26th November 2013) - Chairat, Rungnapa; Puttisri, Adisorn; Pamarapa, Asani; Moollaor, Jirause; Tawichasri, Chamaiporn; Patumanond, Jayanton
Abstract : Objective . To explore prognostic characteristics for locoregional recurrence, distant recurrence, and mortality in patients with breast cancer. Methods . A 5-year retrospective review of patients was conducted in two university affiliated hospitals in the north of Thailand. Prognostic characteristics and clinical outcomes were retrieved from medical registry. Death was verified by the civil database from the Ministry of Interior, direct telephone contact, or by prepaid postcard. Data were analyzed by stratified Cox's regression proposed by Lunn & McNeil, in which multiple-typed outcomes were analyzed in a single multivariable model. Results . The assembled cohort comprised 829 patients. Under the multivariable analysis, 7 prognostic characteristics were significant prognostic indicators. Positive axillary lymph nodes >3 and presence of lymphovascular invasion (LVI) increased locoregional recurrence, while disease stage 3, positive axillary lymph nodes >3, and radiotherapy increase distant recurrence. Hormonal therapy reduced the distant recurrence. Pathological tumor size >2 cm, disease stage 3, positive axillary lymph nodes >3, and presence of LVI increased, while hormonal therapy and chemotherapy reduced death. Conclusions . Clinical characteristic reflecting tumor invasions increased locoregional recurrence, distant recurrence, or death, while hormonal therapy and chemotherapy reduced such risks. The effect of radiation remained inconclusive but may increase the risk of distant recurrence.